A new Lycaste (Orchidaceae: Maxillariinae) from Costa Rica - Bogarín, Diego (Lankesteriana: International Journal on Orchidology, 2007)
Lycaste bruncana from Costa Rica is described and illustrated. This species is sister to L. tricolor, its closest relative, from which is easily distinguished by the lip shape, with a narrow isthmus and spathulate midlobe, the lanate to lanulose infrastigmatic surface, the pollinarium with a longer stipe, the subrectangular pollinia and the tomentose anther cap. However, among Costa Rican species of Lycaste, the most remarkable character of L. bruncana is the twisted column, which may be indicative of a reproductive barrier. Information related to biogeography, distribution, morphology, molecular data and pollination is provided and discussed.